STUDIES ON THE EMULSIFYING PROPERTIES OF GUM RESIN OF SHOREA ROBUSTA N.K. SARATHCHANDRAPRAKASH, M.VIJAYAKUMAR, K. MANRAL, - N.K. SARATHCHANDRAPRAKASH; M.VIJAYAKUMAR; K. MANRAL; U.V.BABU; D.VISHAKANTE. GOWDA (International Journal of Pharma and Bio Sciences, 2015)
In recent years, the importance of natural emulsifiers has increased considerably due to the safety concerns associated with synthetic emulsifiers. In this study, gum resin of Shorea robusta was evaluated for its emulsifying property. An emulsion was prepared using S.robustasemi-purified gum resin (HGRS) as an emulsifier (2.0, 3.0 and 4.0% w/w), and a standard emulsion was prepared with the known emulsifier,Glyceryl monostearate (GMS SE).The prepared emulsions were evaluated for rheological properties, especially flow behavior, and they were stored at room temperature for stability studies at various time intervals for three months. Results of the study suggested that the semi-purified gum resin of S.robusta possesses good emulsifying properties. The emulsion formulated from the natural emulsifier was less sensitive to centrifugation, pH and shear stress. Thus, gum resin of S.robusta can be used as a natural emulsifying agent in topical preparations.